Profile of infant deaths in the state of Piauí in the period between 1996 and 2020 (Research, Society and Development, 2023)
Objective: Calculate the Infant Mortality Rate (IMR) and analyze the epidemiological profile of infant deaths in the period between 1996 and 2020 in the State of Piauí. Methodology: This is a quantitative and descriptive epidemiological study. Results: Data from 1996 to 2020 were evaluated and compared, considering the IMR and the epidemiological profile of infant deaths. With regard to cases of infant deaths, there is a slight increase in this indicator, due to 156 more deaths in 2020 compared to the initial year of the study. Regarding the epidemiological profile of infant deaths, pregnancies lasting between 22 and 36 weeks (41.9%), singleton pregnancies (77.1%) and vaginal deliveries (54%), newborns from 0 to 6 days old (55.6%), male (55.7%), brown (50.2%,), with birth weight from 3000 to 3999g (18.2%). As for the variables related to death, 74.7% of deaths occurred after childbirth, 82.9% of deaths occurred in the hospital environment and 66.8% were from preventable causes. Final considerations: During the described period, it is clear that the high infant mortality rates in Piauí allow us to analyze the effectiveness of public policies in coping with deaths, so that they reflect socioeconomic, regional and ethnic-racial inequalities. Finally, in order to reduce child mortality, better prevention and management is needed for both the mother and those responsible for the child, providing society with involvement and awareness of the efforts necessary for care.